Living Deaths: Anthropological Analysis of Death Rites in Paubokol Community, Regency of Lembata, NTT - Hipolitus Kristoforus Kewuel (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
Death is a part of the reality that will come to everyone. It is not a silly reality and it is not the reality that ends one’s life, instead the reality carries oneself to the two-dimensional new life. First, dimension of eternal life that is personally lived by oneself and at the same time related to theology and the religion studies. Second, the dimension of social life among the one’s living family and at the same time related to the realm of customs and culture. By the ethnographic methods, this research is more focused on tracing the practices of death rites to uncover the power of death to revive the community. The results of the research show that the death rites are aimed at the organization for better community to live together. Through the death rites, the relatives are asked to be introspective, open, and ready to reconcile with anyone not only with those who are directly in conflict, but also with all people who are potential for conflict as anticipatory actions.